The influence of supervisor supportive behaviors on subordinate job satisfaction: the moderating effect of gender similarity - García-Cabrera, Antonia Mercedes; Suárez-Ortega, Sonia María; Gutiérrez-Pérez, Francisco Javier; Miranda-Martel, María José (Frontiers in Psychology, 2023)
This paper analyses the influence that different supervisor supportive behaviors have on subordinate job satisfaction, while considering the gender of individuals involved (supervisor and subordinate). The empirical evidence provided by a sample of 29,833 subordinates from 35 European countries collected by Eurofound through the European Working Condition Survey allows us to assert the following. First, subordinate job satisfaction depends on their perceptions about the supportive behaviors provided by their supervisors in terms of respect, giving recognition for a job well done, coordinating work, helping get the job done, and encouraging the professional development of the subordinate. Second, job satisfaction is affected by supervisor gender, although in the opposite direction as hypothesized, such that when the supervisor is a woman, subordinates report lower job satisfaction. Third, also contrary to our expectations, supervisor-subordinate gender similarity reduces, rather than increases, subordinate job satisfaction. Fourth, gender similarity, as expected, weakens the impact of several supervisor supportive behaviors on this job satisfaction (i.e., giving recognition, coordinating work, helping get the job done, and encouraging development). In terms of practical implications, this work suggests that it is advisable for supervisors to show supportive behaviors toward subordinates. In addition, because demonstrating respect at work is not moderated by gender similarity and seems to be the most impactful supportive behavior for enhancing job satisfaction, supervisors should pay particular attention to the respect of subordinates.